“Equality, freedom, solidarity – the issues on which I was raised”: Viena Chilena 73 | 23: an archive for the intergenerational memory of the Chilean diaspora in Vienna, Austria. (Alternautas, 2024)
As part of this special issue, we received this reflective piece from Viena Chilena 73 | 23, a project initiated to record and articulate the history and memory of Chilean exile in Austria and Austrian-Chilean solidarity during the 50 years since the 1973 military coup in Chile. This contribution pieces together elements of the project website, extracts of their archival work and reflections from the project collective.